THE OCCURRENCE OF CONFUSION BY THE USE OF TRADEMARKS IN COMPETITION LAW - Markosyan, Tigran; Aleksanyan, Kristine (State and Law, 2022)
The article is devoted to the study and analysis of the problems of confusion by the use of trademarks as a separate manifestation of unfair competition. The article presents the functions performed by trademarks, highlighting the function of origin as the initial function and thereby determining the need and scope of trademark protection. Based on theoretical sources, legislation, domestic and foreign judicial practices, the paper reveals and analyzes the conditions for the occurrence of confusion by the use of trademarks in competition law, as well as in the context of the issue under consideration, the features of the legal protection of trademarks are presented. In the article, the authors present a number of scientific and practical conclusions that can be guidelines for law enforcement practice, as well as be used for further legislative reform of this institution of competition law.